Transcutaneous spinal stimulation in patients with intrathecal baclofen pump delivery system: A preliminary safety study - Lopez, John; Forrest, Gail F.; Engel-Haber, Einat; Snider, Brittany; Momeni, Kam; Ravi, Manikandan; Kirshblum, Steven (Frontiers in Neuroscience, 2022)
Objective: To determine the effect of transcutaneous spinal stimulation (TSS) on an implanted intrathecal baclofen (ITB) pump in persons with traumatic spinal cord injury (SCI). Design: Prospective clinical trial. Participants: Five individuals with chronic traumatic SCI, >18 years of age, and an anteriorly implanted Medtronic SynchroMed™ II ITB pump delivery system. Intervention: TSS trials with cathode at T11/12, with pump interrogation before, during and after stimulation. Results: There was no evidence of any effect of the TSS in regards to disruption of the ITB pump delivery mechanism. Communication interference with the interrogator to the pump occurred often during stimulation for log transmission most likely secondary to the electromagnetic interference from the stimulation. One individual had elevated blood pressure at the end of the trial, suspected to be unrelated to the spinal stimulation. Conclusion: Based upon this pilot study, further TSS studies including persons with an implanted Medtronic SynchroMed™ II ITB pump can be considered when stimulating at the low thoracic spine, although communication with the programmer during the stimulation may be affected.